Flaked lithics - Wickham-Jones, Caroline (Scottish Archaeological Internet Reports, 2004)
An assemblage of 4913 flaked lithic artefacts was recovered. These comprise a variety of pieces relating to both the manufacture and use of a range of stone tools. The knappers used a range of raw materials, including both very local stone and stone from slightly further afield. Most of the materials '“ chalcedonic silicas, Rhum bloodstone and quartz '“ were brought to site as nodules ready for working, but baked mudstone seems to have come to Camas Daraich mainly as ready-made tools. Knapping techniques included both platform and bipolar knapping. Though much of the assemblage would be at home on any earlier prehistoric site, there are many pieces indicative of a Mesolithic date. These include a range of narrow-blade microliths and the blades.